Maternal and perinatal outcome in abruption placenta in tertiary care center: a record based case series study - Nethaji, Divya T.; Hurakadli, Kirti M.; Duggavathi, Shama P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Abruptio placenta is premature separation of the normally implanted placenta before delivery. It is one of the leading causes of maternal morbidity and neonatal morbidity and mortality, more so because of the difficulty to predict the acute event. It occurs in approximately one in 80 deliveries and remains a significant cause of perinatal mortality and morbidity. Objective of the study was to study maternal and perinatal outcome in cases of abruption. Methods: 42 cases of pregnant women who presented with abruption placenta to HSK hospital and Research Centre, S. Nijalingappa Medical College, a tertiary care centre at Bagalkot, from January 2022 to December 2022. Maternal and perinatal characteristics were retrieved from the case papers. Results: Among 42 cases of abruption 70% delivered vaginally and 30% underwent caesarean section. 84% had preterm delivery. 66% were still born. 21% were case of severe anaemia and required blood transfusion. 1 had maternal mortality. Conclusions: The availability of advanced emergency obstetric care across greater number of referral hospitals has been responsible for decreasing the morbidity and mortality associated with many obstetric conditions. However, the challenge with abruptio placenta is the difficulty of predicting this condition, and hence appropriate management. As of now, early referral to tertiary care centres, better availability of blood and blood products and early interventions have the potential to limit adverse maternal and perinatal outcomes. Research regarding predictors of placental abruption can help in improving maternal and perinatal outcome.